2014
DOI: 10.1111/jeea.12042
|View full text |Cite
|
Sign up to set email alerts
|

Ecology, Trade, and States in Pre-Colonial Africa

Abstract: State capacity matters for growth. I test Bates' explanation of pre-colonial African states. He argues that trade across ecological boundaries promoted states. I find that African societies in ecologically diverse environments had more centralized states. This is robust to reverse causation, omitted heterogeneity, and alternative interpretations of the link between diversity and states. The result survives including non-African societies. I test mechanisms connecting trade to states, and find that trade suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
126
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(128 citation statements)
references
References 71 publications
(95 reference statements)
2
126
0
Order By: Relevance
“…The conditioning set, X i,c ′ , follows Michalopoulos andPapaioannou (2013, 2014) and other related works (e.g., Fenske 2013Fenske , 2014 and includes log land area, log population according to the first post-independence census, indicators for the presence of rivers and lakes, and several geographic, ecological, and natural resource measures. a c denotes country-specific constants that account for countrywide factors that may affect conflict, related to the type of colonial rule, colonial and contemporary institutions, national policies, etc.…”
Section: B Econometric Specification and Estimationmentioning
confidence: 99%
“…The conditioning set, X i,c ′ , follows Michalopoulos andPapaioannou (2013, 2014) and other related works (e.g., Fenske 2013Fenske , 2014 and includes log land area, log population according to the first post-independence census, indicators for the presence of rivers and lakes, and several geographic, ecological, and natural resource measures. a c denotes country-specific constants that account for countrywide factors that may affect conflict, related to the type of colonial rule, colonial and contemporary institutions, national policies, etc.…”
Section: B Econometric Specification and Estimationmentioning
confidence: 99%
“…Across the developing world there has been a large amount of attention given to the influence of colonial institutions in recent years, with a smaller but growing field of study demonstrating the impact of the precolonial period on postcolonial developments ðHjort 2010; Green 2012; Jha 2013Þ. In one recent example of this trend, several scholars have suggested that precolonial political centralization has had an impact on contemporary levels of development within Africa ðGennaioli and Rainer 2007; Michalopoulos and Papaioannou 2013;Fenske 2014;Alsan 2015;Michalopoulos and Papaioannou 2015Þ. Measuring precolonial centralization by using data from Murdock ð1967Þ, they show a robust positive correlation between the percentage of each country's population that is from a centralized ethnic group and outcomes such as light density at night, paved roads, immunization, literacy, and infant mortality rates.…”
Section: Introductionmentioning
confidence: 99%
“…The role of trade on early state formation has been well discussed in the historical, anthropological, political science, and economics literature (Bates, 1983;Fenske, 2014;Service, 1978). Although it is impossible to provide irrefutable empirical evidence on whether it was long-distance or local regional trade that mattered most for the early emergence of statehood, particular emphasis has been placed on the role of long-distance trade as a driver of centralization (Braudel, 1972;Gluckman, 1941;Polanyi, 1957).…”
Section: Division Of Labor Trade and Statehoodmentioning
confidence: 99%
“…Both datasets have been widely used in anthropology and economics for the study on pre-industrial societies and the long-term effects of pre-industrial culture and institutions (Alesina, Giuliano and Nunn, 2013;Fenske, 2014;Gennaioli and Rainer, 2007;Michalopoulos and Papaioannou, 2013). The Ethnographic Atlas (Murdock, 1967) includes information on 115 characteristics for 1267 ethnicities around the globe.…”
Section: Centralizationmentioning
confidence: 99%
See 1 more Smart Citation